Applying ethics to itself: recursive ethical questioning in architecture and second-order cybernetics. Issue 4 (1st April 2019) - Sweeting, Ben
Abstract : Purpose: The purpose of this paper is to put forward a way that ethics may be applied recursively to itself, in the sense that how we speak and reason about ethics is an activity to which ethical considerations and questions apply. Design/methodology/approach: The paper is built on parallels between design and cybernetics, integrating elements of ethical discourse in each field. The way that cybernetics and design can each act as their own meta-disciplines, in the design of design and the cybernetics of cybernetics, is used as a pattern for a similarly recursive approach to ethics. This is explored further by drawing parallels between Heinz von Foersters' criticism of moral codes and concerns about paternalism in designing architecture. Findings: Designers incorporate implicit ethical questioning as part of the recursive process through which they design their design activity, moving between conversations that pursue the goals of a project and meta-conversations in which they question which goals to pursue and the methods they employ in doing so. Given parallels between designing architecture and setting out an ethics (both of which put forward ways in which others are to live), a similar approach may be taken within ethical discourse, folding ethics within itself as its own meta-discipline. Originality/value: The paper provides a framework in which to address ethical considerations within ethical discourse itself. Recursive ethical questioning of this sort offers a way of coping with the incommensurability of values and goals that is commonplace given the fragmented state of contemporary ethics.